Development and Security in Southeast Asia. Vol. 2, The People (David B. Dewitt and Carolina G. Hernandez, eds.) - Domingo, Sarah Jane (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Review of Development and Security in Southeast Asia. Vol. 2, The People (David B. Dewitt and Carolina G. Hernandez, eds.).
Keywords: Development; Security; Southeast Asia; People